Implementation of the Integration of Science and Islam in Islamic Education: Strategies for Building a Non-Dichotomy Paradigm - Eko Nursalim; Hasan, Hasan (At-Taqaddum, 2025)
This research responds to the real challenges in madrasahs, where low integration of Islamic knowledge with scientific education is hindered by limited teacher competencies and inadequate learning facilities. Using a library research method supported by case studies of Islamic Religious Education laboratories, this study aims to clarify the objectives and relationship between science and Islam as well as the challenges and practical solutions for integration. Findings show that integration is a complementary process where science strengthens religious understanding (faith), while Islam guides the objectives and orientation of human endeavors. Practical strategies include interdisciplinary curriculum development, teacher training to improve qualifications, and establishing Islamic Religious Education laboratories that use natural phenomena as learning media. These laboratories serve as places for practising and researching Islamic teachings, enhancing students’ competence and stimulating scientific attitudes. The study’s implications offer concrete benefits for educators by providing effective teaching strategies, for students by fostering a holistic worldview connecting material and spiritual dimensions, and for policymakers by informing policies and programs supportive of science-Islam integration in educational institutions. This integrative approach is vital for developing comprehensive education in madrasahs that addresses contemporary educational and spiritual needs, enhancing learning quality and educational infrastructure.